Kompres Hangat untuk Mengatasi Masalah Hipertermia pada Penderita Kejang Demam: Warm Compress to Address Hyperthermia in Febrile Seizure Patients - Kusuma, Rohmah Dini Nur; Suryani, Roro Lintang; Cahyaningrum, Etika Dewi (Journal of Nursing Education and Practice, 2023)
Background: A child is someone who is less than 18 years old in a period of growth and development, with special needs, namely physical, psychological, social and spiritual needs. Children are more susceptible to infections that often cause a high fever. Fever is not a disease but a symptom. Fever often occurs at the age of five, when the increase in body temperature reaches the highest number scale, it will cause seizures in children which are called febrile seizures. One of the nursing problems in patients with febrile seizures that need special treatment is hyperthermia. Management of hyperthermia in febrile seizures can be done non-pharmacologically, namely by giving warm compresses. Purpose: To reduce body temperature in An. S with a diagnosis of febrile seizures in the Ar Rahman Room, RSI Purwokerto. Method: Descriptive research design in the form of a case study with a nursing process approach consisting of assessment, formulating diagnoses, interventions, implementation and evaluation. Data collection techniques using observation, interviews, physical examination and documentation. This case study was conducted on An. S for 3x24 hours. Result: Nursing care is carried out to An. S is 9 months old and has hyperthermia problems carried out in 3x24 hours, the procedures used for the assessment are observation, interviews, physical examination and documentation. Evaluation on the third day of red skin, seizures, and body temperature has resolved. Conclusion: Warm compresses have been shown to be effective in overcoming the problem of hyperthermia in patients with febrile seizures